Transcriptomic Identification and Biochemical Characterization of HmpA, a Nitric Oxide Dioxygenase, Essential for Pathogenesis of Vibrio vulnificus - Kim, Dukyun; Na, Eun Jung; Kim, Suhyeon; Kim, Jung Sung; Jung, Young Hyun; Cao, Jiafu; Han, Ho Jae; Bang, Iel Soo; Yoo, Jin-Wook; Ha, Nam-Chul; Choi, Sang Ho (Frontiers in Microbiology, 2019)
Nitric oxide (NO) and its derivatives are important effectors of host innate immunity, disrupting cellular function of infecting pathogens. Transcriptome analysis of Vibrio vulnificus, an opportunistic human pathogen, identified a set of genes induced upon exposure to NO. Among them, VvhmpA (V. vulnificus hmpA), encoding a multidomain NO dioxygenase, was the most greatly induced upon exposure to NO and was thus further characterized. Absorption spectra demonstrated that VvHmpA is a heme protein in which the heme iron can exist in either reduced, NO-bound, or oxidized state. Biochemical studies revealed that VvHmpA is a flavohemoglobin containing equimolar amounts of heme and FAD as cofactors. The KM and kcat values of VvHmpA for NO at 37 °C, the temperature encountered by V. vulnificus in the host, were greater than those at 30 °C, indicating that VvHmpA detoxifies high levels of NO effectively during infection. Compared with the wild type, the VvhmpA mutant exhibited a lower NO-decomposition activity and impaired growth in the presence of NO in vitro. Also, the cytotoxicity and survival of the VvhmpA mutant infecting the NO-producing murine macrophage cells were lower than those of the wild type. Furthermore, the mouse lethality of the VvhmpA mutant was reduced compared to that of the parental wild type. The combined results revealed that VvHmpA is a potent virulence factor that is induced upon exposure to NO and important for the survival and pathogenesis of V. vulnificus during infection.